Effect of Fat Substitution on the Rheological and Textural Properties of Raw Chicken Meat Emulsion and Cooked Patties - Chappalwar, Anita; Pathak, Vikas; Goswami, Meena; Verma, Arun Kumar; kumar, V. Raj (Journal of Meat Science, 2023)
The present study was conducted to evaluate the rheological behaviour  and textural properties of raw chicken meat emulsion and cooked patties respectively. Low fat chicken emulsions were prepared with the addition  of pre-optimized levels of 1%lemon albedo, 2% mango peel powder,  and 2% banana peel powder with the replacement of 50% vegetable  oil in formulation The rheological behaviour of low fat emulsion and  textural properties of these low fat emulsion based chicken patties were  observed. The formulation of chicken meat emulsion was maintained by  the addition of water with the replacement of fat. Dynamic oscillatory  measurements revealed the weak gel formation of emulsions with  addition of fat replacers, as storage modulus values (G΄) were higher than  the loss modulus values (G˝). Chicken meat patties were prepared from  these low fat chicken meat emulsions. Textual profile analysis of cooked  patties showed a significant (P
Keywords: Fat substitution; Chicken meat emulsion; Lemon albedo powder; Mango peel powder; Banana peel powder; Rheological characteristics; Textural Properties